2016
DOI: 10.1016/j.amjcard.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Prevalence and Outcomes of Atrial Fibrillation in Patients Hospitalized With Heart Failure

Abstract: Previous research has shown that roughly 15% to 30% of those with heart failure (HF) develop atrial fibrillation (AF). Although studies have shown variations in the incidence of AF in patients with HF, there has been no evidence of mortality differences by race. The purpose of this study was to assess AF prevalence and inhospital mortality in patients with HF among different racial groups in the United States. Using the National Inpatient Sample registry, the largest publicly available all-payer inpatient care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…From this perspective, the real status of anticoagulation is rather discouraging. Previously, we found a similar phenomenon11 in which a cardioversion and catheter ablation were significantly underutilized in minority ethnic groups.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…From this perspective, the real status of anticoagulation is rather discouraging. Previously, we found a similar phenomenon11 in which a cardioversion and catheter ablation were significantly underutilized in minority ethnic groups.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, among patients with HF and AF, minority racial groups were shown to underutilize treatment and have disproportionately higher risks of inpatient death11. In regards to treatment strategies, studies have shown that ethnicity may affect anticoagulation81012 and cardiac ablation13 in patients with AF.…”
mentioning
confidence: 99%
“…In the National Inpatient Sample registry, an inverse correlation of AF with diabetes in Asian patients with HF was seen; among whom those with AF had less diabetes compared with those without (41% vs 52%, p<0.001) 7. In the GWTG-HF Registry, patients with HF and diabetes had a lower prevalence of chronic or recurrent AF than those without diabetes (32% vs 38%, p<0.001), although patients from this registry were predominantly white (69% vs 2% Asian) and separate analyses between different ethnicities were not performed 20.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Bathia et al had previously described a higher proportion of whites in patients with HF and AF when compared with blacks, Asians and Hispanics, but had the lowest rate of diabetes, hypertension, cardiomyopathy, hyperthyroidism and second lowest rate of obesity, all of which are well-recognised risk factors of AF 7. Findings from our study are in agreement, suggesting that the higher prevalence of AF among white patients may be due to an inherent ethnicity-specific characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Beyond traditional risk factors, there is growing evidence of ethnic influences on the prevalence of AF in the context of HF. [3][4][5][6][7] A large US registry reported a higher prevalence of AF among white HF patients compared with blacks, Hispanics, and Asians 3 ; while a prospective Asia Pacific study showed a distinctly lower prevalence of AF among Singaporean-Asian compared with New Zealand European HF patients. 5 The ethnic differences in AF prevalence in HF, while striking, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%